Two major sudden stratospheric warmings during winter 2023/2024 - Lee, Simon Haydn; Butler, Amy; Manney, Gloria L. (Weather, 2025)
Major sudden stratospheric warmings (SSWs) occur in the Arctic around six times per decade. During winter 2023/2024, two major SSWs occurred – a relatively rare event, having occurred on average only once per decade. Here, we summarise the evolution of the two SSWs, their dynamics and impacts on stratospheric chemical processing and tropospheric weather patterns. While both SSWs were displacement events, they evolved remarkably differently. The 16 January SSW was short-lived and did not exert a canonical influence on surface weather. In contrast, the 4 March SSW followed a more typical evolution, albeit with only weak coupling to the troposphere.